Two versions of hybridity: blood mixing representation of Tirso de Molina y en el Inca Garcilaso de la Vega - Jensen, Julio Hans C. (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
Through the analysis of two works of the Spanish Golden Age, the drama Amazonas en las Indias by Tirso de Molina and the historical work Comentarios reales de los incas by Inca Garcilaso de la Vega, the present article aims to illustrate the understanding of America as a hybrid region. Amazonas en las Indias is interpreted through Deleuze and Guattari’s theory (Capitalisme et schizophrénie. L’Anti-Œdipe) of the presence of the oedipal figure in a capitalistic structure of social production. The Comentarios reales are understood as the creation of a both individual and collective narrative identity (a notion coined by Paul Ricoeur). In this way the ethnic and cultural hybridity becomes, as well from a psychoanalytic as from a discursive perspective, a feature of the newly discovered and conquered continent. This characteristic can be considered a prefiguration of the subsequent historical development of a non-ethnocentric, hybrid notion of culture and thought.